Combination Effect of NK and P Fertilizers on Soil Available-K, K Absorption, and Sweet Corn Productivity in Inceptisols - Emma Trinurani Sofyan; Muhammad Amir Solihin; Oviyanti Mulyani; Annisya Salsabilla; Asty Nesya; Irwandhi Irwandhi (Institut Pertanian Bogor, 2025)
One factor affecting sweet corn's (Zea mays saccharata Sturt.) productivity refers to soil fertility and proper fertilization. This study aimed to determine the optimal combination of NK and P fertilizer doses to enhance the growth and yield of corn grown on Inceptisols. This research was conducted at the Soil Chemistry and Plant Nutrition Experimental Field, Faculty of Agriculture, Universitas Padjadjaran. The Randomized Block Design consisted of 10 treatments with three replicates each. The treatments included: A, control; B, standard NPK; C, ¼ dose NK + 1 P + ½ N; D, ½ dose NK + 1 P + ½ N; E, ¾ dose NK + 1 P + ½ N; F, 1 dose NK + 1 P + ½ N; G, 1¼ dose NK + 1 P; H, 1 dose NK; I, ½ dose NK + ½ single N,P,K; and J, ¾ dose NK + ¼ single N,P,K. The results showed that the combination of NK and P fertilizers significantly affected the growth and yield of sweet corn. The treatment with ¾ NK + 1 P + ½ N had a notable impact on cob weight (0.33 kg/cob), cob diameter (5.05 cm), and cob length (21.2 cm). This treatment also increased K absorption to 34.49, available soil K to 2.45 cmol kg-1, and the sweetness level of corn to 13.56%. This study provides new recommendations for corn fertilization to improve the growth and yield on Inceptisols. Keywords: optimal fertilizer dosage, corn growth, corn productivity, nutrient uptake